Internet Access and Use among Students of Physical Education: A Study of Kurukshetra University, Kurukshetra - Kumar, Rajender (Journal of Information Science Theory and Practice, 2014)
This paper depicts a study conducted on the behavior of physical education students towards Internet usage at Kurukshetra University, Kurukshetra. Specially, the study aims to know the purposes for use of Internet resources and services, frequency of use, places and means of use, student's satisfaction level toward the Internet, and problems faced while using the Internet. A survey was carried out with a sample of 100 physical education students of Kurukshetra University and the response rate was 88%. A well-designed questionnaire was distributed to the students' sample. Amazingly, the results of the study reveal that usage of the Internet in research and education was not favored, whereas email, chatting, and sports websites were commonly used among students. The study also found that too much information on the Internet, slow access speeds, and finding relevant information were the main problems in using the Internet.